Morphometric study of the porcine placental vascularization. (6th November 2017) - Cristofolini, A; Fiorimanti, M; Campos, M; Sanchis, E; Diaz, T; Moschetti, E; Merkis, C
Contents: The early development in mammals is characterized by the contribution of nutrients from the maternal tissues through the placenta, which is in apposition with foetal membranes and the endometrium, allowing the physiological interchange between the embryos/foetuses and the mother. The aim of this work was to study the number of placental blood vessels and their vascular area through morphometric analyses and the haemotrophic diffusion distance in porcine placental tissues from early gestations, intermediates gestations, advanced gestations and term gestations. For those purposes, morphometric measurements, blood vessel quantification, high‐resolution light microscopy and transmission electron microscopy were performed. The implementation of the high‐resolution light microscopy allowed studying the placental vascular and tissue histoarchitecture with higher definition and resolution than using a conventional light microscopy. We highlight the close location of the subepithelial capillaries to the maternal/foetal interface as pregnancy progresses. We found statistically significant evidence to state that the area of blood vessels is dependent on the gestation period. In advanced gestations, the presence of numerous small blood vessels and its near location to foetal/maternal interface agree with the great remodelling reported in our previous studies. In conclusion, in gilts, given the type of non‐invasive epithelial placentation, the new blood vessels generation and of haemotrophic diffusion distance reduction, determined in this report, assure the maternal/foetal haemotrophic exchange efficiency during gestation.